The role of antecedent and consequent events in sustainable behavior - Corral Verdugo, Victor; Domínguez Guedea, Rosario Leticia (Mexican Journal of Behavior Analysis, 2011)
A review of the pertinent literature shows that the interest of most environmental psychologists focuses on studying the antecedent events (i.e., historical-and-situational dispositional variables) that promote sustainable behavior. This behavior is defined as the set of actions aimed at conserving the Earth’s natural and socio-cultural resources, so that the wellbeing of present and future generations can be guaranteed. Although several psychological frameworks –eminently the behaviorist- acknowledge the importance of the positive consequent variables (i.e., positive repercussions) on the display and maintenance of sustainable behavior, a limited interest in their study is detected, especially in regard to the role played by intrinsic consequences. Since a number of those consequences have been recently reported in research reports, this paper discusses how the positive repercussions might promote the display of sustainable lifestyles and how the antecedent events could be connected with the consequent ones, so that a higher likelihood of generating pro-environmental and pro-social behaviors among citizens may be achieved. The paper also reviews a possible way of connecting individual proenvironmental behavior with the cultural practice of sustainable actions